Experimental research on the corrosion of X series pipeline steels under alternating current interference. (August 2017) - Guo, Yanbao; Meng, Tao; Wang, Deguo; Tan, Hai; He, Renyang
Abstract: Many buried oil and gas pipelines are parallel to the high-voltage transmission lines and electrified railways in a long distance. Alternating current (AC) corrosion of these pipelines are very significant in such cases, and might lead to leakage even serious accidents. Laboratory experiment was carried out through weight-loss method in a simulated soil solution at various AC densities from 0 to 200 A/m 2 and frequencies from 10 to 200 Hz. The results indicated that the corrosion rate increased with the increasing of AC current density. Furthermore, with the increase of AC interference frequency, the AC current involved in the electrode reaction process is decrescent, which caused a lower corrosion rate of pipeline steel. Morphology and corrosion product investigations explained that a better anti-corrosion behavior of X80 than that for X60 and X70 under AC interference. The investigation results are benefit to provide a new strategy to forecast and evaluate of the AC-induced corrosion, and design of the buried X series oil/gas pipelines. Highlights: Laboratory experiment was carried out through weight-loss method in a simulated soil solution for AC corrosion. The presence of AC interference accelerated the corrosion of X pipeline steel. Corrosion rate increased with the increasing of AC current density, and decreased with the AC interference frequency.